Analisis Framing Berita Pemasangan Radio Frequency Identification (RFID) di Kompas.com dan Republika.co.id - Nugroho Tri Putra (Universitas Islam Negeri Imam Bonjol Padang, 2014)
The installation of radio frequency identification RFID became appeal to the mass media to be reported. The mass media that lift the news were Kompas.com and Republika.co.id. Each mass media had its own framing proclaimed it to the public. This study used framing analysis models Zhongdang Pan and Gerald M. Kosicki. In this study, the researchers found there was no difference in the news framing done by Kompas.com and Republika.co.id.in news RFID installation. Kompas.com tended to preach a balance of information patterns, whereas Republika.co.id was bolder and more critical in presenting the news. Besides, Kompas.com looked to give a positive image to the installation of an RFID program, while the Republika.co.id wanted to show the facts that occurred in the field of RFID implementation had many obstacles and complaints.